(untitled) - Gschwandtner, Gerhard (New York, 2007)
This book introduce about understanding success, understanding your customers, understanding yourself
Keywords: Selling,Success in business,Bán hàng,Thành công trong kinh doanh; Psychological aspects,Psychological aspects,Khía cạnh tâm lý,Khía cạnh tâm lý